Application technique: placement of a prostate-rectum spacer in men undergoing prostate radiation therapy - Hatiboglu, Gencay; Hadaschik, Boris; Hohenfellner, Markus (BJU international, 2012)
Study Type - Therapy (case series) Level of Evidence 4 What's known on the subject? and What does the study add? Different spacing agents have been tested to reduce incidential radiation exposure of the rectum during radiotherapy to the prostate. These agents all had certain drawbacks; either the created space was too small or the agents used did not stay in place during radiotherapy treatment. The study describes the transperineal injection technique of a spacing agent in detail. Furthermore it shows the safety and efficacy of the spacing hydrogel used and shows that it overcomes some of the drawbacks of the previously examined spacing agents. OBJECTIVE • To describe the technique used to apply a hydrogel spacer between the prostate and rectum so as to decrease the radiation dose to the rectum in patients with prostate cancer who are undergoing radiotherapy. METHODS • A prospective study evaluating the safety and efficacy of prostate-rectum spacer injection was conducted in 29 male patients with prostate cancer scheduled for radiotherapy. • Spacing hydrogel was injected into the perirectal space using a transperineal approach under real-time transrectal ultrasonography guidance. • With the needle tip positioned beyond the rectourethralis muscle, saline injection opened the space between Denonvilliers' fascia and the anterior rectal wall, allowing needle advancement to the mid-prostate without rectal wall injury. Injection of hydrogel precursors further opened this space, which was then maintained as a result of hydrogel polymerization. • Procedure duration and adverse events were monitored. Computed tomography and/or magnetic resonance imaging simulation scans were performed before and after injection. The hydrogel-created space was measured and the reduction in percent volume of the rectum receiving at least 70 Gy (rectal V70) was determined. RESULTS • Hydrogel injection resulted in mean (sd) additional prostate-rectum space relative to baseline of 9.87 (5.92) mm. • The mean (sd) procedure time, as measured by needle insertion and removal, was 6.3 (3.2) min. • The relative reduction in rectal V70 was 60.6%. • There were no unanticipated adverse events associated with the hydrogel procedure or the hydrogel. CONCLUSIONS • Hydrogel spacer injection using hydrodissection is a fast and effective procedure to separate the rectal wall from the prostate in order to avoid rectal toxicity. • Hydrogel spacer injection resulted in the addition of ∼1 cm of space • Computed incidental radiation exposure, the rectal V70, was substantially reduced.